Rectal Prolapse and Cystic Fibrosis. Issue 1 (January 2015) - El-Chammas, Khalil I.; Rumman, Nisreen; Goh, Vi Lier; Quintero, Diana; Goday, Praveen S.
<x xml:space="preserve">Abstract</x> ABSTRACT Screening for cystic fibrosis (CF) is suggested in patients with rectal prolapse (RP). Little is known about the association between CF and RP in the era of newborn screening for CF. Our retrospective review showed that 3.6% of patients with RP had CF, and 3.5% of patients with CF had RP. No demographic or clinical factors appear to predict the likelihood of RP in patients with CF. Sweat chloride testing for patients with RP has a low yield in the era of newborn screening but may still need to be considered in children with RP to avoid missing the rare child with CF.